ANALISIS STRUKTUR MODAL DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hutagalung, Windi; Syukrina, Viola (LPPM Universitas Putera Batam, 2021)
The study is shown to analyze the structure of the capital and turnover of inventory on the profitability of companies manufaktu r are listed on the Stock Exchange Indonesia. The population in the study this is a company manufacturing sub- sectors of food and beverages are listed on the Stock Exchange Indonesia is 26 da n use sample as much as 7 corresponding criteria are set out in the sample . Mechanical collection of data in the form of documentation and put the source of data sekuder were obtained from reports of financial year 2016-2020 are listed on the Stock Exchange Indonesia. Mechanical analysis of the data used in the study is that the test statistic to test Assuming the classical form of test for normality , multicollinearity , test heterokedasitas , and test autocorrelation and using the test regression linear multiple which consists of test t and test F, and Test The coefficient of determination (R ²) by using SPSS version 25. Based on the results of testing the structure of capital effect on profitability and Inventory turnover has an effect on profitability . in the same time , the structure of capital and perputa ran supplies affect profitability . Keywords: Capital Structure, inventory turnover, Profitability (ROA)